2019
DOI: 10.1029/2019ja026976
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Energetic Neutral Atom Emissions and the Ground‐Based Geomagnetic Indices: Implications From IBEX Observations

Abstract: We report the first daylong continuous observations of bright terrestrial energetic neutral atom (ENA) emissions by the Interstellar Boundary Explorer (IBEX). The unique vantage point of IBEX, up to ∼48 Earth radii (Re) from the dawn‐dusk side, allowed it to monitor ENAs from 0.3 to 6.0 keV over an unprecedented length of time. We have taken advantage of this capability to discover correlations between auroral electrojet (AE) indices and ENA emissions. Although it was difficult to separate the source from low‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 83 publications
(137 reference statements)
0
9
0
Order By: Relevance
“…The same applies for the N-lobe and S-lobe, as shown. Interestingly, this squeezing phenomenon has also been observed to happen in the Earthʼs magnetosphere (Sibeck et al 1985), and most recently, the squeezing and rotation of the magnetotail as a function of the interplanetary magnetic field clock angle has been reported using IBEX magnetospheric observations (e.g., Hart et al 2021 for IBEX magnetospheric ENA imaging; see also Fuselier et al 2010;McComas et al 2011;Dayeh et al 2015Dayeh et al , 2020bOgasawara et al 2019;Starkey et al 2022).…”
Section: Lobes' Relative Locations In the Heliotailmentioning
confidence: 79%
“…The same applies for the N-lobe and S-lobe, as shown. Interestingly, this squeezing phenomenon has also been observed to happen in the Earthʼs magnetosphere (Sibeck et al 1985), and most recently, the squeezing and rotation of the magnetotail as a function of the interplanetary magnetic field clock angle has been reported using IBEX magnetospheric observations (e.g., Hart et al 2021 for IBEX magnetospheric ENA imaging; see also Fuselier et al 2010;McComas et al 2011;Dayeh et al 2015Dayeh et al , 2020bOgasawara et al 2019;Starkey et al 2022).…”
Section: Lobes' Relative Locations In the Heliotailmentioning
confidence: 79%
“…Early observations of such energetic neutral atoms (ENA) from Earth's magnetosphere from ENA imagers onboard the IMAGE satellite were used to study the development of the ring current during substorms and storm times (e.g., Brandt et al, 2002;DeMajistre et al, 2002;Denton et al, 2005;Pollock et al, 2001). Newer measurements from the Two Wide-Angle Imaging Neutral-Atom Spectrometers (McComas, Allegrini, Baldonado, et al, 2009) mission instrument and the Interstellar Boundary Explorer (IBEX; McComas, Allegrini, Bochsler, et al, 2009) spacecraft have enabled the study of global features of Earth's magnetosphere, in addition to substorm and storm time development (e.g., Dayeh et al, 2015Dayeh et al, , 2020Fuselier et al, 2010Fuselier et al, , 2015Fuselier et al, , 2020Hart et al, 2021;McComas et al, 2011McComas et al, , 2012Ogasawara et al, 2013Ogasawara et al, , 2015Ogasawara et al, , 2019Petrinec et al, 2011;Starkey et al, 2022;Valek et al, 2010). In particular, Fuselier et al (2010Fuselier et al ( , 2020 used IBEX observations to image the shocked SW plasma at the magnetopause and showed that ENA spectra from the subsolar magnetosheath are representative of the ion distributions from which they originate (for energies >0.1 keV; see also Ogasawara et al, 2013).…”
Section: Of 10mentioning
confidence: 99%
“…At a certain fixed point in space, these ENAs can be observed remotely, enabling global imaging of this region. Similar ENA imaging has been exploited extensively to understand the physical processes in different parts of the Earth's magnetosphere (e.g., Dayeh et al, 2015 et al., 2011;Ogasawara et al, 2015Ogasawara et al, , 2019. Furthermore, ENA remote sensing continuously images the region of interest over multiple spatial scales, hence simultaneously viewing emissions from different portions of the region of interest (Dayeh et al, 2015;Ogasawara et al, 2019).…”
Section: Global Perspective Of the Foreshock Regionmentioning
confidence: 99%